Edivoxetine compared to placebo as adjunctive therapy to selective serotonin reuptake inhibitors in the prevention of symptom re-emergence in major depressive disorder. (6th May 2015) - Oakes, Tina M.; Dellva, Mary Anne; Waterman, Karen; Greenbaum, Michael; Poppe, Christopher; Goldberger, Celine; Ahl, Jonna; Perahia, David G.
Abstract: Objective: When patients with major depressive disorder (MDD) are partial responders to antidepressant therapy, adjunctive treatment with an agent that has a different mode of action may provide additional benefit. We investigated the efficacy of edivoxetine, a highly selective norepinephrine reuptake inhibitor (NRI), as adjunctive treatment to selective serotonin reuptake inhibitors (SSRIs) in the prevention of re-emergence of depressive symptoms in patients with MDD (ClinicalTrials.gov identifier: NCT01299272). Methods: Adult outpatients with MDD who were partial responders to SSRI treatment ( N = 1249) entered an open-label 8 week flexibly dosed (12–18 mg/day) adjunctive edivoxetine period. Patients who achieved remission (Montgomery–Åsberg Depression Rating Scale total score ≤10 at week 8) entered a 12 week open-label fixed-dose (12 mg or 18 mg/day) stabilization period, and those still in remission at each of weeks 18, 19, and 20 were randomized to continue treatment at the same dose of edivoxetine or switch to placebo for a 24 week double-blind withdrawal period. All patients remained on SSRI therapy throughout the study. The primary outcome was time to re-emergence of depressive symptoms during double-blind withdrawal. Results: Two hundred and ninety-four patients were randomized to continue adjunctive edivoxetine and 292 were switched to adjunctive placebo. Comparing adjunctive edivoxetine with adjunctive placebo, differences were not significant for time to re-emergence of symptoms (Kaplan–Meier log-rank p = 0.485), rates of symptom re-emergence (9.9% vs 8.2%, p = 0.565) or rates of sustained remission (75.4% vs 76.7%, p = 0.771). Treatment-emergent adverse events were consistent with the noradrenergic mechanism of action. Conclusions: Edivoxetine failed to demonstrate superiority vs placebo as adjunctive treatment in the prevention of symptom re-emergence during maintenance treatment in SSRI partial responders with MDD. While no selective NRIs are approved for adjunctive treatment to SSRIs in MDD, the use of NRIs in this population is nonetheless accepted practice, but our data do not support the efficacy of this approach.